World Economy Spring 2016 - Clouded outlook for the world economy - Klaus-Jürgen Gern; Philipp Hauber; Nils Jannsen; Stefan Kooths; Martin Plödt; Maik H. Wolters (Kiel Institute for the World Economy (IfW), 2016)
Global growth has slowed down recently. While the world economy should gradually regain pace over the coming quarters, overall growth momentum is expected to remain subdued. The recent drop in oil prices has not improved the outlook as it to a substantial degree signals weaker demand; additionally, lower prices will continue to be a drag on activity in oil-exporting countries. Increased uncertainty is also weighing on growth. Against this backdrop, our forecast for world economic growth in 2016 has been revised down by half a percentage point to 2.9 percent. For 2017 we forecast global GDP growth of 3.5 percent (December: 3.7 percent). Activity in advanced economies will be supported by rising income and expansive monetary policies. Emerging economies, however, face both structural and cyclical headwinds. Although the current dismal performance is expected to improve over the forecast horizon, growth will remain low by historical standards. – – Die weltwirtschaftliche Dynamik hat sich zuletzt abgeschwächt. Im weiteren Verlauf dieses Jahres und im nächsten Jahr dürfte die Weltwirtschaft zwar allmählich wieder an Fahrt gewinnen, doch bleibt die konjunkturelle Dynamik vorerst gering. Durch die niedrigeren Ölpreise haben sich die Aussichten für die Weltkonjunktur nicht verbessert. Sie reflektieren nicht zuletzt eine schwache Nachfrage, zudem sind die dämpfenden Wirkungen in den Ölexportländern beträchtlich. Gebremst wird die Konjunktur derzeit außerdem durch eine erhöhte wirtschaftliche Unsicherheit. Die Zunahme der Weltproduktion gerechnet auf Basis von Kaufkraftparitäten wird in diesem Jahr mit einer Rate von 2,9 Prozent noch etwas geringer ausfallen als im vergangen Jahr. Damit haben wir unsere Prognose vom Dezember um 0,5 Prozentpunkte reduziert. Für das kommende Jahr erwarten wir einen Zuwachs der Weltproduktion um 3,4 Prozent (Dezember: 3,7 Prozent). In den fortgeschrittenen Volkswirtschaften erhöht sich angesichts verstärkt zunehmender Einkommen und einer weiterhin sehr expansiven Geldpolitik sukzessive die konjunkturelle Dynamik. In den Schwellenländern sind die wirtschaftlichen Probleme vielfach nicht nur konjunktureller sondern struktureller Natur. Hier dürfte sich die derzeit sehr schwache, zum Teil sogar rezessive Entwicklung im Prognosezeitraum zwar verbessern, im längerfristigen Vergleich bleibt der Produktionsanstieg aber sehr moderat.
Additional information: Short English version, full version available only in German language.
Keywords: 330; Brexit; global oil market; Oil price shocks; United States; potential output; Output gap; advanced economies; emerging economies; Japan; Russia; ASEAN